Introduction: Inclusive and Student-Centred Learning in Linguistics and Translation - Costanza Cucchi; Mirella Piacentini (MediAzioni)
Introduction to the dossier Inclusive and Student-Centred Learning in Linguistics and Translation: Practices in Higher Education.